KINETIKA REAKSI ESTERIFIKASI n-OKTIL p-METOKSI SINAMAT (OPMS) - Suyatno, ; Titik Taufikurohmah, ; Nurul Hidajati, (Matematika dan Sains, 2011)
The aim of research was to study the chemical kinetic of esterification of ester derivided from cinnamic acid, namely octyl-p-methoxy cinnamate. It was synthesized from ethyl-p-methoxy cinnamate isolated from kencur tuber and n-octanol. Results showed that esterification of octyl-p-methoxy cinnamate proceeded through first order reaction and its activation energy was 1530 Joule/ mol.